Pengaruh Persepsi Kegunaan, Kemudahan Penggunaan, dan Keamanan terhadap Minat Menggunakan Fintech Payment pada Generasi Z di Sidoarjo - Fadilla, Alivia Irza; Prapanca, Detak (Jurnal EMT KITA, 2026)
The rapid development of digital technology has accelerated the adoption of fintech payment services, particularly among Generation Z who are highly familiar with digital platforms. However, users’ intention to adopt fintech payment is strongly influenced by their perceptions of usefulness, ease of use, and security. This study aims to analyze the effects of perceived usefulness, perceived ease of use, and perceived security on the intention to use fintech payment among Generation Z in Sidoarjo Regency. This research employs a quantitative approach using purposive sampling, involving 200 respondents who have used fintech payment services for at least three months. Data were collected through online questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results indicate that perceived usefulness, perceived ease of use, and perceived security have poitive and significant effects on the intention to use fintech payment. Among these variables, perceived usefulness has the most dominant influence on usage intention. These findings support the relevance of the Technology Acceptance Model (TAM) in explaining financial technology adoption behavior among Generation Z and provide practical implications for fintech service providers to improve service quality, system usability, and security features to encourage sustainable usage, especially in suburban areas such as Sidoarjo Regency.